THE PENSION SYSTEM IN UKRAINE: CURRENT TRENDS AND DEVELOPMENT PROSPECTS - DOTSENKO, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the consideration of topical issues of the pension provision system in Ukraine and determination of its development in modern conditions. To achieve this research goal, the following methods were used: methods of analysis and synthesis; abstract and logical method; methods of theoretical generalization and systematization. The article defines the content, role and principles of pension provision. The system of pension provision in Ukraine under martial law is assessed. The main problems of the functioning of the solidarity level of pension provision are identified. The critical role of funded pension insurance in the pension system is substantiated and the problems of its implementation in Ukraine under martial law are investigated. The place and role of non-state pension provision in ensuring the welfare of Ukrainian citizens are determined. Prospects for the development of the non-state pension system are considered. The following main directions of development of the non-state pension insurance system are proposed: increasing public confidence in the non-state pension system, expanding the potential of the stock market for the efficient use of pension assets of accumulative pension programs, improving the legislative framework, forming an effective system of protection of pension assets, and introducing individual pension accounts in banking institutions. The tools for implementing the proposed areas of development of non-state pension provision are: the introduction of a system of disclosure of information about non-state pension funds, the creation of a single state body to control the activities of non-state pension funds, mandatory financial risk insurance, which increases the level of guarantees for depositors, investment in liquid low-risk instruments in circulation, and the implementation of international financial reporting standards.